Effect of different cooking temperature and time of glutinous rice flakes - Noordin, Mohd Ikram; Mohd Dom, Zanariah; Shamsudin, Rosnah; Hashim, Norhashila (HH Publisher, 2022)
The immature stage of glutinous paddy or Oryza sativa var. glutinosa is one of the most popular cultivars known as waxy or sticky. Glutinous rice flake is a flattened carbohydrate-rich edible food obtained from the processing of immature glutinous paddy. Since glutinous rice flake is a traditional food, the farmers are more comfortable producing it by conventional cooking. Still, it will take longer and require more labor energy. Hence, this study aims to determine a new cooking method for glutinous rice flake using a microwave oven at different temperatures (230oC, 240°C, 250°C) and ranging taken (3.3min, 4.0min, 4.3min, 5.0min, 5.3min). From the study, the suitable cooking parameter is at a temperature of 250oC, from 4.3min to 5.0min. The glutinous paddy can maintain its stickiness and is easy to flatten. Furthermore, the husks are easily removed and separated from the paddy grains during the flattened process. Lower temperatures and shorter time taken will make the paddy not fully cooked. However, higher temperatures and longer time will make the paddy pop and easily break. In short, this study successfully identifies the new cooking parameter of rice flake by implementing microwave heat treatment. The physical, frictional and chemical properties of rice flake through microwave heat treatment can be considered for further study.